Papa is a poet : a story about Robert Frost - Bober, Natalie S. (Henry Holt and Company, 2013)
"When Robert Frost was a child, his family thought he would grow up to be a baseball player. Instead, he became a poet. His life on a farm in New Hampshire inspired him to write 'poetry that talked,' and today he is famous for his vivid descriptions of the rural life he loved so much. There was a time, though, when Frost had to struggle to get his poetry published. Told from the point of view of Lesley, Robert Frost's oldest daughter, this is the story of how a lover of language found his voice"--